Does One Treatment Fit All? Effectiveness of a Multicomponent Cognitive Behavioral Therapy Program in Data-Driven Subtypes of Perinatal Depression - Waqas, Ahmed; Rahman, Atif (Frontiers in Psychiatry, 2021)
Background The prevalent diagnostic systems of psychiatric disorders are criticized for their poor validity and reliability, owing to the within disorder heterogeneity and between disorder homogeneity. However, little focus has been put on perinatal depression. i) Quantify heterogeneity attributable to the polythetic diagnostic framework for perinatal depression and ii) Present evidence for the effectiveness of a multicomponent and low-intensity cognitive behavioural Thinking Healthy Programme (THP) across the heterogeneous presentations for the PND. Methods This investigation presents secondary analyses of a cluster randomized controlled trial, conducted in the Kallar Syedan, Pakistan. A total of 903 pregnant women either randomized to the intervention group receiving the THP programme or control group receiving enhanced care. Principal component analyses and clustering algorithm were utilized to identify heterogenous subtypes of PND. Linear mixed effects models were used to assess effectiveness of the intervention across the identified subtypes of PND. Results Four different clusters of PND were identified: mixed anxiety-depression, somatic depression, mild depression, and atypical depression. All clinical phenotypes responded well to the THP programme. Compared to their counterparts in the control group, mothers with mild depression in the treatment group yielded lowest risk ratios 0.24 (95% CI: 0.15 to 0.37), followed by mothers with anxiety-depression 0.50 (95% CI: 0.37 to 0.68), atypical depression 0.51 (95% CI: 0.27 to 0.99) and somatic depression 0.59 (95% CI: 0.42 to 0.83). Conclusion The Thinking Healthy Programme was found to be effective in reducing severity of depressive symptoms and disability across the four subtypes of PND.